2005
DOI: 10.1182/blood.v106.11.4797.4797
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes in Adult T Leukemia/Lymphoma: Report of 55 Cases from Peru.

Abstract: Adult T -cell leukaemia/lymphoma (ATL) is an aggressive disease associated with human T-cell lymphotropic virus type-I (HTLV-I) with heterogeneous clinical presentation and outcomes, described in Southern Japan, Europe, Caribbean and previously on Pacific coast of South America including Peru (EHA 2001, abst. 304). Shimoyama’s ATL classification (BHJ1991:79) includes four types: acute, lymphomatous, chronic and smoldering; recently a new clinical type cutaneous had been described (BJD2005:152). Herein we show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Previous studies have indicated that the frequency of primary malignant neoplasms in HTLV-1 carriers is higher than in HTLV-1 seronegative non-Hodgkin lymphoma cases [ 19 ]. HTLV-1 infection is strongly associated to the development of ATLL and several Peruvian studies on clinical characteristics and outcomes of patients with ATLL have been reported [ 20 ]. Although HTLV-1 has not been associated with the development of B-cell lymphomas, HTLV-1 carriers with B-cell lymphoma tend to have a worse prognosis [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have indicated that the frequency of primary malignant neoplasms in HTLV-1 carriers is higher than in HTLV-1 seronegative non-Hodgkin lymphoma cases [ 19 ]. HTLV-1 infection is strongly associated to the development of ATLL and several Peruvian studies on clinical characteristics and outcomes of patients with ATLL have been reported [ 20 ]. Although HTLV-1 has not been associated with the development of B-cell lymphomas, HTLV-1 carriers with B-cell lymphoma tend to have a worse prognosis [ 21 ].…”
Section: Resultsmentioning
confidence: 99%